Inventory and Identification of Natural Dyes of Ikat Woven Fabrics at Sanggar Bliran Sina Watublapi - Rosdewi, Maria; Sada, Mariana; Fitriah, Fitriah (Jurnal Riset Ilmu Pendidikan, 2023)
The aim of this research is to find out kinds of plants that produce natural dye toward traditional woven, part of the plant that used in the process of producing natural dye traditional woven from the plant in Bliran Sina workshop, Watublapi. The research is held on Watublapi on April 13th until June 13th 2021. The approach of this study was descriptive qualitative method with the step of gathering information with explorative survey technique, observation, interview, and documentation. Based on the result of the research found 9 various plants that used as the resources of natural dye for the traditional woven such as Manggoo plant (Mangifera Indica L), Mas Candle(Pachystachys lutea Nees), Tarum (Indigofera tinctoria L), Runner bean (Phaseolus ceccineus L), Mahogany (Swietenia mahoni L), Katuk (Sauropus androgynus L) Noni Plant (Morinda citrifolia L), Greedy (Symplocos fasciculata Zoll), and Tumeric (Curcuma domestic Val) also 3 additional plants that is used in the oiling process before the thread smeared with the natural dye like papaya (Carica papaya L), Candlenut (Aleurites molucana L), Angel’s Trumpet (Bignonia capreolata L). parts of the plants that used for natural dye are the roots, leaves, cortex, and rhizome. Most part of the plants that being used is leave which is 65% and the cortex is 22%, and the part of the plant which is less used are rhizome and the roots which is 11% each. The step of the process is done in different way such as pounded, submerged, and cooked. Based on the process that have been done there are 11 color have been produced such as; black, dark blue, light blue, yellow, light green, dark green, dark brown, light brown, and yellowish red, pink, and red. Those are homemade natural dye